Reinforcement bar measurement in structural concrete using Ground Penetrating Radar method / Mohd Redzwan Mat Sah - Mat Sah, Mohd Redzwan (2005)
Rebar diameter in structural concrete is an important parameter for a structural engineer to calculate the strength of certain construction. For construction, the critical area for structure is at beam, column and slab. At present only Radiography is the reliable and accurate non-destructive method for rebars diameter determination. However, radiography requires accessibility for placement of radiation source and film from both side of the object to be tested and this is not applicable for certain concrete member such as floor slab. In GPR technique, a Handisearch RC Radar NJJ-85A has been used to measure bar sizing in five different type of concrete. It is observed that a concrete containing bars with a separation distance of 200mm has shown more accurate result, whereby the one containing bars with separation distance of 100mm exhibited dimension which are two or more times smaller than the actual diameter. Observations on the sample containing bar with different height revealed that result are not affected by the depth of the bar from the surface. GPR can be considered as a reliable and accurate non-destructive method for rebars diameter determination if a technique to interpret the hyperbolic curve can be established.